Educational Opinion Writing Webinar For Teachers - Wahyu Fatihah; Sonny Rohimat; Dail Maruf; Neli Fori Karliana; Muhamad Alwi; Dedeh Mayasari; Muhyidin Muhyidin (Abdimas Paspama, 2024)
The literacy competency that is being intensively promoted by the Ministry of Education and Culture is not only aimed at students, but also at their teachers. Following up on this, IGI Kota Serang held a webinar with the theme of improving the ability of teachers to write opinions at various levels of education. The aim of the webinar is to increase teacher competency in literacy, especially in the field of writing, which will be followed up with the publication of an opinion anthology book in the field of education. The steps taken in implementing the webinar activities are forming a committee, looking for resource persons, preparing webinar requirements, socializing activities, implementing activities, as well as evaluation and reflection. Based on the results of evaluation and reflection, the implementation of the webinar went smoothly but there were a few obstacles in sending the certificate because the documents sent exceeded the capacity of the Autocrat add-on.